P.Y. Galperin's Development of Human Mental Activity Lectures in Educational Psychology - Engeness, Irina (Cultural Psychology of Education, 2021)
This open access book introduces the legacy of Piotr Galperin to a wider audience of researchers, educators and psychologists. Previous translations of Galperin's work present only some aspects of his conceptual thinking; however, his main contribution to the general, genetic and pedagogical psychology as a unique holistic and systemic approach to studying of psychological phenomena and processes, mechanisms of their formation and development, is still quite unknown in most parts of the world. The eight lectures chosen for the book have been translated from Russian for the first time, and they belong to the Study of the Formation of Human Mental Activity from Galperin's collection of the Lectures in Psychology (Galperin, 2002). These eight lectures present the central ideas of Galperin's pedagogical theory, and they conceptualise learning to learn approach and argue how teaching and learning process can enhance the development of higher mental functions with learners and therefore enhance the development of students as learners. These ideas may be of primary importance to educational practitioners and researchers interested in developmental learning and teaching approach given the current concerns of educational practice that schools struggle to prepare students for their adult and the need to develop the capacity in lifelong learning with students in the 21st century.